La utilización de estrategias metodológicas y su incidencia en el desarrollo cognitivo de los niños y niñas de preparatoria primer grado de educación general básica de la escuela "William Caxton College" ubicada en el sector de Ponciano Alto de la ciudad de Quito, periodo lectivo 2013-2014 - Serrano Chicaiza, Silvana Paola (2014)
This research entitled "USE OF METHODOLOGICAL STRATEGIES AND ITS IMPACT ON THE BÁSIC GENERAL EDUCATION FIRST YEAR CHILDREN COGNITIVE DEVELOPMENT " WILLIAM CAXTON COLLEGE” SCHOOL LOCATED IN THE FIELD OF PONCIANO ALTO SECTOR QUITO, CITY.PERIOD 2013-2014 ". IT IS STRUCTURED ON THE BASIS OF CURRENT GUIDELINES GRADUATION AT THE NATIONAL UNIVERSITY. The general objective that Loja guided the research process was: To determine the incidence of the Methodology Using Cognitive Development Strategies in children’s the basic general education first year The methods used were: Scientist, Inductive, Deductive, Analytic-Synthetic, Descriptive and Statistical Model. The techniques applied were: Survey applied to the teachers in order to identify the Methodological Strategies used in the daily work with children first year; and Cognitive Skills Test applied to first year; and Basic General Education of ; and Observation guide for the the type of methodological strategy used for cognitive Development. A cording to the teachers survey applied was that: 100% of teachers surveyed choose the following Methodological Strategies used in everyday day with children: the game, art, children's literature, visual graph, 67% projects and workshops. According to the results of the Test of Cognitive Skills, 81% children’s have investigated Cognitive Development and Very Satisfactory Unsatisfactory 19%. With the implementation of the Observation Guide is concluded that: 85% of teachers do use different types of Methodological Strategies for Cognitive development and 15% don’t use.